2018
DOI: 10.1016/j.amsu.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Case report of a conservative management of cervical esophageal perforation with acrylic glue injection

Abstract: Backgroundperforation of the upper aerodigestive tract is a potentially life-threatening condition. The appropriate treatment of cervical esophageal perforation is still controversial.Case presentationwe report a case of cervical esophageal perforation that was effectively treated by a conservative management with acrylic glue injection.Discussionthe management of cervical esophageal perforations has been controversial and little studied. Various treatment options, including surgical and nonsurgical management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Between other applications of CA, the treatment of upper and lower gastrointestinal fistulas was one of the most interesting. A few case reports were presented in the literature [54][55][56][57]. In details, Anoldo et al [54] reported a case of cervical esophageal perforation that was successfully treated with CA injection after the failure of other conservative options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between other applications of CA, the treatment of upper and lower gastrointestinal fistulas was one of the most interesting. A few case reports were presented in the literature [54][55][56][57]. In details, Anoldo et al [54] reported a case of cervical esophageal perforation that was successfully treated with CA injection after the failure of other conservative options.…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports were presented in the literature [54][55][56][57]. In details, Anoldo et al [54] reported a case of cervical esophageal perforation that was successfully treated with CA injection after the failure of other conservative options. Thus, it was possible to consider CA a promising minimally invasive alternative for the treatment of cervical esophageal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin has tissue-healing properties and is used for sealing, and cyanoacrylate can be used with clips to ensure closure. 17 Anoldo et al 69 described a fast recovery with the application of cyanoac-rylic glue into the fistula opening in a case of an iCEP. They attributed this favorable result to the glue's adhesive and hemostatic properties, high tensile resistance, and antibacterial characteristics.…”
Section: Endoscopic Managementmentioning
confidence: 99%
“…However, conservative management with glue is not recommended if the output from the fistula is of high volume exceeding 500 mL in 24 hours. 69 Endoscopic vacuum-assisted closure is also a recent novel technique. It is used to drain mediastinal abscesses and involves positioning a small sponge placed with the help of an endoscope that suctions with a negative-pressure pump.…”
Section: Endoscopic Managementmentioning
confidence: 99%
See 1 more Smart Citation